Metabolomics analysis of stool in rats with type 2 diabetes mellitus after single-anastomosis duodenal–ileal bypass with sleeve gastrectomy - Wang, Lun; Wang, Zeyu; Yu, Yang; Ren, Zhaoheng; Jia, Yongheng; Wang, Jinfa; Li, Shixing; Jiang, Tao (Frontiers in Endocrinology, 2022)
Background Single-anastomosis duodenal-ileal bypass with sleeve gastrectomy (SADI-S) is one of the most effective bariatric procedures in the treatment of type 2 diabetes mellitus (T2DM). However, the mechanisms by which SADI-S improves T2DM are not well-known. Objective To explore the effects of SADI-S on metabolites in the stool of rats with T2DM. Methods Nineteen rats were fed on high-fat diet and administered with a low-dose (30mg/kg) of streptozotocin to establish T2DM models. The rats were then randomly assigned to the SADI-S group (n=10) and sham operation group (n=9). Stool samples were collected from all rats 8 weeks after surgery and stored at -80 °C. Metabolomics analysis was performed to identify differential metabolites through ultra- performance liquid chromatography-mass spectrometry. Results At 8-weeks after surgery, rats of the SADI-S group showed significantly decreased fasting blood glucose, glucose tolerance test 2-hour, glycated haemoglobin, and body weight compared with those of the sham group. A total of 240 differential metabolites were identified between the two groups. Among them, 16 metabolites such as branched-chain amino acids (valine), aromatic amino acid (phenylalanine), bile acid (cholic acid, lithocholic acid, and β-muricholic acid), short-chain fatty acid (isobutyric acid), and phospholipid [lysoPE(17:0), lysoPE(20:3) and lysoPS(16:0)] were associated to the T2DM remission after SADI-S. Conclusion SADI-S improves T2DM in rats by regulating phenylalanine biosynthesis, valine, phenylalanine, alanine, glutamate, proline, bile acid, and phospholipid metabolism pathways.